The smashed man of Dread End - Ocker, J. W. (Harper, an imprint of HarperCollinsPublishers, 2021)
"Noe Wiley couldn't be more excited to move. After the slumber party sleepwalking incident of last year, she's ready to make some new friends. But Noe didn't expect the sullen, strange girls who live on her new street. And she certainly didn't expect the strange warning they give her--to stay out of her basement, no matter what. Noe's not going to let these girls boss her around. She'll go in her own basement whenever she wants. So she does. And there he is. And now there's no going back"--